Effectiveness of phototherapy with reflecting curtains on neonatal jaundice - Ari Kurniasih; Guslihan Dasa Tjipta; Muhammad Ali; Emil Azlin; Pertin Sianturi (Indonesian Pediatric Society, 2011)
Background Although phototherapy has been used in clinical practice for 40 years, there is still much debate on how to provide the most efficacious phototherapy. Phototherapy with white reflecting curtains may increase the average spectral irradiance provided, as well as decrease serum bilirubin concentrations at a faster rate in neonates with jaundice.Objective To determine if adding low cost, white, reflecting curtains to a standard phototherapy unit can increase the effectiveness of phototherapy for neonatal jaundice.Methods A randomized, controlled, open trial was conducted at H. Adam Malik and Pirngadi Hospitals, Medan, from May to December 2009. The criteria for inclusion in the study were full term newborns with neonatal jaundice presenting in their first week of life. Single phototherapy with white curtains hanging from the sides of the phototherapy unit (study group, n=30) was compared to single phototherapy without curtains (control group, n=30). The primary outcomes measured were the mean difference in total serum bilirubin levels and average spectral irradiation levels measured at baseline, and after 12 hours and 24 hours of phototherapy.Results The sum of average spectral irradiance in the curtained phototherapy unit was significantly higher than that of the standard phototherapy unit without curtains (P < 0.05). The decrease of total serum bilirubin levels after 12 and 24 hours of phototherapy was significantly greater in the study group (3.71 and 9.7 mg/dl, respectively) than in the control group (0.1 and 3.8 mg/dl, respectively), both P <0.05.Conclusion White, reflecting curtains in phototherapy units was significantly more effective than phototherapy without curtains for treatment of neonatal jaundice. [Paediatr Indones. 2011;51:256-61].